Community building on the Web - Kim, Amy Jo (Peachpit guide to webtop publishing., 2000)
What's the point of creating a great Web site if no one goes there-or worse, if people come but never return? How do some sites, such as America Online, EBay, and GeoCities, develop into Internet communities with loyal followings and regular repeat traffic? How can Web page designers and developers create sites that are vibrant and rewarding? Amy Jo Kim, author of Community Building on the Web and consultant to some of the most successful Internet communities, is an expert at teaching how to design sites that succeed by making new visitors feel welcome, rewarding member participation, and building a sense of their own history. She discusses important design strategies, interviews influential Web community-builders, and provides the reader with templates and questionnaires to use in building their own communities.